A Delphi yarn: applying Indigenous knowledges to enhance the cultural utility of SMART Recovery Australia - Elizabeth Dale; Katherine M. Conigrave; Peter J. Kelly; Rowena Ivers; Kathleen Clapham; K. S. Kylie Lee (Addiction Science & Clinical Practice, 2021)
Abstract Background Mutual support groups are a popular treatment for substance use and other addictive behaviours. However, little is known about the cultural utility of these programmes for Indigenous peoples. Methods A three-round Delphi study, utilising Indigenous research yarning methods was conducted to: (1) Obtain expert opinion regarding the cultural utility of an Indigenous SMART Recovery handbook; (2) Gain consensus on areas within the SMART Recovery programme that require cultural modification and; (3) Seek advice on how modifications could be implemented in future programme design and delivery. The panellists were 11 culturally, geographically, and professionally diverse Indigenous Australian health and wellbeing experts. A group consensus level of 80% was set prior to each survey round. Results There was 100% participant retention across all three Delphi rounds. The panel reached consensus on five key programme modifications (composition of a separate facilitator and group member handbook; culturally appropriate language, terminology, and literacy level; culturally meaningful programme activities; supplementary storytelling resources; and customisation for diverse community contexts). The panel also developed a series of practical implementation strategies to guide SMART Recovery through a modification process. Conclusion The findings highlight the importance of involving Indigenous peoples in the design, delivery and validation of mainstream mutual support programmes. Indigenous-led programme modifications could help improve accessibility and usefulness of mutual support groups for Indigenous peoples worldwide. This study is an example of how Indigenous research methods can be used alongside the Delphi technique. This approach demonstrated a way that Indigenous peoples from culturally and geographically diverse locations can participate in research anonymously, autonomously and without added burden on personal, community or professional obligations.